Astragalus Polysaccharides and Saponins Alleviate Liver Injury and Regulate Gut Microbiota in Alcohol Liver Disease Mice - Jingxuan Zhou (MDPI AG, 2021)
Astragalus, a medical and edible plant in China, shows several bioactive properties. However, the role of astragalus in attenuating alcoholic liver disease (ALD) is less clear. The objective of this project is to investigate the improving effect of astragalus saponins (AS) and astragalus polysaccharides (AP), which are the two primary constituents in astragalus on hepatic injury induced by alcohol, and the potential mechanisms of action. Different doses of AS (50 and 100 mg/kg bw) and AP (300 and 600 mg/kg bw) were orally given to alcohol-treated mice for four weeks. The results demonstrated that both AP and AS could reverse the increase of the levels of TC, TG, FFA, and LDL-C in serum, and the decrease of serum HDL-C content, as well as the elevation of hepatic TC and TG levels induced by alcohol. The activities of AST, ALT, ALP, and γ-GT in ALD mice were raised after AP and AS supplementation. The antioxidant markers (SOD, CAT, GSH, and GSH-Px) were obviously augmented and the pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β) and hepatic histological variations were alleviated by AP and AS, which was in line with the levels of oxidative stress-associated genes (Keap1, Nfe2l2, Nqo1, and Hmox1) and inflammation-associated genes (Tlr4, Myd88 and Nfkb1). In addition, AS exerted a more efficient effect than AP and the results presented dose proportionality. Moreover, AS and AP could modulate the intestinal microbiota disturbance induced by alcohol. Overall, AS and AP administration could ameliorate lipid accumulation in the serum and liver, as well as hepatic function, oxidative stress, inflammatory response, and gut flora disorders in mice as a result of alcohol.